2022
DOI: 10.1103/physrevmaterials.6.083801
|View full text |Cite
|
Sign up to set email alerts
|

Simple machine-learned interatomic potentials for complex alloys

Abstract: Developing data-driven machine-learning interatomic potentials for materials containing many elements becomes increasingly challenging due to the vast configuration space that must be sampled by the training data. We study the learning rates and achievable accuracy of machine-learning interatomic potentials for many-element alloys with different combinations of descriptors for the local atomic environments. We show that for a five-element alloy system, potentials using simple low-dimensional descriptors can re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…In our previous study, a ML Gaussian approxima-7 tion potential (GAP) was developed to describe two- ter descriptor [64] and EAM is a descriptor correspond-19 ing to the pairwise-contributed density used in embedded 20 atom method potentials [63] (see Supplementary Infor- The validation of the soapGAP and tabGAP is shown 43 in Fig. 2, where both potential energies and force compo- The standard deviations of the force error distribution are σ tabGAP ≃ 3.33σ soapGAP , similar to that of the energy errors.…”
mentioning
confidence: 99%
“…In our previous study, a ML Gaussian approxima-7 tion potential (GAP) was developed to describe two- ter descriptor [64] and EAM is a descriptor correspond-19 ing to the pairwise-contributed density used in embedded 20 atom method potentials [63] (see Supplementary Infor- The validation of the soapGAP and tabGAP is shown 43 in Fig. 2, where both potential energies and force compo- The standard deviations of the force error distribution are σ tabGAP ≃ 3.33σ soapGAP , similar to that of the energy errors.…”
mentioning
confidence: 99%
“…2c). The comparison moreover shows that the UNEP-v1 model trained against 1-component and 2-component structures also performs very well for 3-component [34], 4-component [33], and 13component [32] structures extracted from the datasets in the previous studies [32][33][34]. The testing RMSEs of the UNEP-v1 model for these three datasets are respectively 57 meV/ Å, 196 meV/ Å, and 258 meV/ Å, which are com- parable to those reported as training RMSEs in the original publications [32][33][34].…”
Section: Resultsmentioning
confidence: 94%
“…The good accuracy of defects description, combined with high computational efficiency, indicates that the proposed ADP can be used to study a variety of materials scientific problems, such as diffusion or mobility of defects in pure metals and CCAs. The validation of pure metal properties showed that among the interatomic potentials of the W-Mo-Nb system, only the tabGAP model [43] can compete with the developed ADP. Overall, ADP provides a more accurate description of molybdenum and niobium, and tabGAP reproduces the properties of tungsten with better accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Results for the EAM potential of Nb are taken from published works [15,61]. Also, we included in this validation part a comparison of classical potentials with recently developed advanced ML-models for RAs: SNAP [40], MTP [41] and tabGAP [43].…”
Section: Properties Of Pure Metalsmentioning
confidence: 99%
See 1 more Smart Citation